Fear of Death and Supernatural Beliefs: Developing a New Supernatural Belief Scale to Test the Relationship. Issue 5 (14th January 2013) - Jong, Jonathan; Bluemke, Matthias; Halberstadt, Jamin
Abstract : Fear of death features in both historical and contemporary theories of religion, but the relationship between death anxiety and religious belief is still ambiguous, largely due to the use of inappropriate or imprecise measures. The current studies therefore aimed to develop a valid, targeted measure of respondents' tendency towards religious belief, the 'Supernatural Belief Scale' (SBS), and to use the SBS to examine the relation between death anxiety and religious belief. Results indicate that the SBS shows high reliability and convergent validity and that its relation to death anxiety depends on participants' religious identification: 'religious' participants fear death less the stronger their religious beliefs, whereas 'non‐religious' participants are more inclined towards religious belief the more they fear death. These studies contribute a new measurement tool for research on religious belief and provide a starting point for an experimental integration of discrepant research findings. Copyright © 2013 European Association of Personality Psychology